Management of the Acute Scrotum in a District General Hospital: 10-Year Experience - Lukas Tajchner; John O. Larkin; Michael G. Bourke; Ronan Waldron; Kevin Barry; Paul W. Eustace (The Scientific World Journal)
The acutely painful scrotum is a common urologic emergency. The primary objective of management is to avoid testicular loss. This requires a high index of clinical suspicion and prompt surgical intervention. In our series conducted between January 1996 and December 2005, 119 patients (age range: 4–62 years) underwent emergency operative exploration for acute scrotal pain. The most common finding was torted cyst of Morgagni (63/119, 52.9%), followed by testicular torsion (41/119, 34.4%). The majority of testicular torsions occurred in the pubertal group (22/41, 53.6%). Only one patient in this group had an unsalvageable testis necessitating orchidectomy, a testicular loss rate in torsion of 2.4%. There were no postoperative wound infections or scrotal haematomas. Testicular salvage depends critically on early surgical intervention, so the delay incurred in diagnostic imaging may extend the period of ischaemia. Furthermore, all radiological investigations have a certain false-negative rate. We advocate immediate surgical exploration of the acute scrotum. We report a low orchidectomy rate (2.4%) in testicular torsion.